The Highly Conserved Glycan at Asparagine 260 of HIV-1 gp120 Is Indispensable for Viral Entry - François, Katrien O. (American Society for Biochemistry and Molecular Biology, 2011)
Carbohydrate-binding agents bind to the N-glycans of HIV-1 envelope gp120 and prevent viral entry. Carbohydrate-binding agents can select for mutant viruses with deleted envelope glycans. Not all glycosylation motifs are mutated to the same extent. Site-directed mutagenesis revealed that deletions destroying the highly conserved (260)NGS(262) glycosylation motif resulted in non-infectious virus particles. We observed a significant lower CD4 binding in the case of the N260Q mutant gp120 virus strains, caused by a strikingly lower expression of gp120 and gp41 in the virus particle. In addition, the mutant N260Q HIV-1 envelope expressed in 293T cells was unable to form syncytia in co-cultures with U87.CD4.CXCR4.CCR5 cells, due to the lower expression of envelope protein on the surface of the transfected 293T cells. The detrimental consequence of this N-glycan deletion on virus infectivity could not be compensated for by the creation of novel glycosylation sites near this amino acid, leaving this uncovered envelope epitope susceptible to neutralizing antibody binding. Thus, the Asn-260 glycan in the gp120 envelope of HIV-1 represents a hot spot for targeting suicidal drugs or antibodies in a therapeutic effort to efficiently neutralize a broad array of virus strains.